Aplikasi theory of planned behavior (TPB) dalam intensi pembelian apartemen di wilayah Jakarta dengan domisili sebagai variabel moderating - KLEMENS WEDANAJI PRASASTYO (Jurnal Bisnis dan Akuntansi, 2015)
The purpose of this paper is to analyze the influence of Theory of Planned Behavior with variables taken attitudes, subjective norms, and perceived behaviour toward purchase intension of apartment in Jakarta territory, adn using domicile as a moderating variable. The respondents are Manager up level who work in Jakarta and have the income not less than twenty million rupiah per month. Based on 119 questionners collected, the results shows that there is positif significant influence between attitudes, subjective norms, and perceived behaviour toward purchase intension of apartment in Jakarta territory. Domicile was not found to have moderating effect on the relationship between all independent variables and the purchase intension ofa apartment in Jakarta territory. This study contributes to and extends our understanding of the apartment purchasing behavior, identifying the rationales for purchasing of apartement in Jakarta territory.